(untitled) (Theatrum historiae, 2019)
The correspondence of Michal Institoris Mossotzy (preacher of the Slovak-Hungarian committee of the Augusburg religion in Bratislava) from the end of the 18th century, stored in the manuscript collections of the Lyceal library in Bratislava, conceals rich information about the early years of the tolerance period of the forming evangelical committees in Bohemia and Moravia. One of the problems these archives capture is attempts to create a generation of pastors based on the home environment, who were supposed to ensure stability in the new choruses. This work presents attempts to educate six boys (future preachers) coming from five churches of the Augsburg religion to the evangelical lycée in Bratislava. Although the boys came from a financially strong environment and had Mossotzy’s support, their studies did not usually end successfully. The boys fled after even several years of study, eager to join the army, take over their parents’ businesses or break up completely with the evangelical church. The causes of failure in creating the first Czech generation of preachers can be seen in the immaturity of the boys, the distance from home and the adventurous environment of a city.